Analysis on the Dynamic Behavior of Space Shafting under Combined Load - Yan Zhao; Fei Gao; Yulei Xia; Jinfang Gu; Yameng Wang; Sen Zhao (Shock and Vibration)
The space shafting is the core component of the momentum exchange attitude control actuator for spacecraft.The dynamic behavior of space shafting has an important impact on the performance of the actuators. Based on the dynamic theory of rolling bearing, this paper presents a dynamic analysis model of space shafting for the interaction between bearing balls and oil-containing nonmetallic cage under combined loads. Also, the accuracy of the analysis model was verified through a high-speed camera system to conduct a cage speed test. In addition, the dynamic behavior of balls and cage under combined loads and the interaction between them is also analysed. The results show that the axial displacements of balls fluctuate periodically under combined loads, and the rotation speeds of balls and cage are easily affected by the load, presenting as the oscillation of speed. Also, the force between balls and cage increases as the load increases. The dynamic behavior of balls and cage could be effectively improved by avoiding excessive torque loads and limiting the axial preload to 40 N. The wear failure caused by unstable operation of bearings cannot be ignored. This model is more practical in completing simulation analysis of different operating conditions and structural parameters of the shafting system. It provides a theoretical reference for the structural design and performance analysis of space shafting.